Perancangan Interior International Culinary School di Surabaya - Edward Leonard; Andereas Pandu Setiawan (Intra, 2018)
Food as the basic needs of human life has made the culinary world a developing business. With the design of culinary school facilities, the objective of this design project is to create an interior environemnt that can support the quality learning activities that can compete with the contemporary culinary world. This culinary school design project was inspired by the concept of